Pematahan Dormansi Benih Gmelia arborea Roxb. Menggunakan Asam Sulfat (H2SO4) - Suhartati, Tatik; Taat Andayani, Surodjo; Wahyudiono, Sugeng (Jurnal Wana Tropika, 2022)
Gmelina (Gmelina arborea Roxb.) seed is a type of seed that have physical dormancy. This is because water and gases prevent by the hard seed coat during the germination process. Therefore, to break dormancy, preliminary treatment in the form of scarification is required, including using sulfuric acid (H2SO4) solution. This study aims to determine the treatment of soaking in a 96% concentration of H2SO4 solution that produces the best germination ability. The study used a completely randomized design method (CRD) with 5 soaked time treatments, namely control (0 minutes), 5 minutes, 10 minutes, 15 minutes, 20 minutes and each treatment was repeated 3 times with 50 seeds for each replication. The results showed that soaked the seeds in the 96% concentration of H2SO4 solution had a significant effect on on initial time of germination, last time of germination, 80% limit time for germination, percentage of germination and vigor index. Soaking time for 10 minutes is the best treatment for scarification of gmelina seeds.   Keywords: physical dormancy; pre-treatment; scarification; soaking time